Determinan Kinerja Usaha Mikro (Studi Pada Usaha Mikro Di Kecamatan Wenang, Manado) - Paskanova Christi Gainau (Universitas Katolik Darma Cendika, 2020)
Nowadays, regarding increasing number of micro-business in urban areas, achieving competitive advantage is considered as one of the business concerns. Obtaining competitive advantage entails specific requirements that social capital, physical capital, and human capital - is regarded as one of the most important factors. This study aims to examine the effect of capital to the performance of microbusinesses. The sample of this study was 31 micro-businesses in Wenang subdistrict, Manado, who were selected by simple random sampling. After distributing the questionnaires, the data analysis was done by SmartPLS 3.0 M3. The result show that social capital and physical capital had no significant effect on the performance of micro-business, while human capital had a positive, and significant effect on the business performance. The implication is the Manado City government has to make the labor of micro-business as the target of empowerment activities that are organized by the government, private sector, bank, NGOs, domestic or foreign. In the long term, it can drive the micro-industry to the small and medium industries.